2010
DOI: 10.1007/s00726-010-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes regulated by ammonium availability in the roots of maritime pine trees

Abstract: Conifers have a preference for ammonium over nitrate as the main inorganic nitrogen source. However, it is unknown how changes in nitrogen nutrition may affect transcription profiles. In this study, microarray analysis and suppressive subtraction hybridization were used to identify differentially expressed genes in the roots of maritime pine exposed to changes in ammonium availability. A total of 225 unigenes that were differentially regulated by changes in ammonium nutrition were identified. Most of the unige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
5
35
0
Order By: Relevance
“…More recently the role of AMP1 in maritime pine has been linked to N acquisition. Excess ammonium induces the expression of AMP1 [24], and functional analyses performed with purified protein supports the function of AMP1 in the regulation of ammonium ion flux into pine roots [106]. These results highlight the connections between pathogen attack and N metabolism, a topic that warrants further research efforts.…”
Section: Biotic Interactionssupporting
confidence: 52%
See 2 more Smart Citations
“…More recently the role of AMP1 in maritime pine has been linked to N acquisition. Excess ammonium induces the expression of AMP1 [24], and functional analyses performed with purified protein supports the function of AMP1 in the regulation of ammonium ion flux into pine roots [106]. These results highlight the connections between pathogen attack and N metabolism, a topic that warrants further research efforts.…”
Section: Biotic Interactionssupporting
confidence: 52%
“…It has been found that the ammonium regulated AMP1 protein [24,106] is also upregulated at the early stages of ectomycorriza formation and therefore might be involved in the regulation of N transfer from ectomycorrizal fungi to plant hosts [115]. Following transfer at the mycorrhizal interface, N is incorporated into the amides glutamine and asparagine [115].…”
Section: Biotic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest levels of AMP transcripts were present in the apex, with lower abundances in other sections, except for a peaking bulk in section 4, which represented about 30% of the maximal observed expression. AMP1 is a member of the plant AMP b-barrelin family and could have a role in the regulation of ammonium nutrition in maritime pine roots (Canales et al 2010(Canales et al , 2011. In contrast, the LPT and MT genes were almost exclusively expressed in the upper part of the stem, suggesting that they are mainly associated with the function of meristematic cells.…”
Section: Validation Of Differentially Expressed Genes In the Stem By mentioning
confidence: 96%
“…In a recent paper, we investigated the effects of ammonium availability on the transcriptome of maritime pine roots using a combination of microarray analysis and suppressive subtraction hybridization (Canales et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%